2022
DOI: 10.1111/ene.15412
|View full text |Cite
|
Sign up to set email alerts
|

A real‐world evidence study of nabiximols in multiple sclerosis patients with resistant spasticity: Analysis in relation to the newly described ‘spasticity‐plus syndrome’

Abstract: Background and purpose: Nabiximols is a therapeutic option for patients with multiple sclerosis (MS) spasticity whose symptoms are poorly controlled by conventional oral firstline medications. This study aimed to assess the relationship between changes in spasticity severity (measured on the 0-10 numeric rating scale [NRS]) and the presence of associated symptoms in patients treated with nabiximols, and to investigate the presence of the newly described 'spasticity-plus syndrome'. Methods:We analyzed real-worl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 38 publications
(72 reference statements)
2
8
0
Order By: Relevance
“…The largest clusters were of spasticity, spasms/cramps and pain, and the cluster of those three symptoms plus fatigue. Pain was the symptom most frequently associated with spasticity, as also found in other studies ( 14 , 20 ). In this study, pain was more common in RRMS patients but the difference was not statistically significant.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The largest clusters were of spasticity, spasms/cramps and pain, and the cluster of those three symptoms plus fatigue. Pain was the symptom most frequently associated with spasticity, as also found in other studies ( 14 , 20 ). In this study, pain was more common in RRMS patients but the difference was not statistically significant.…”
Section: Discussionsupporting
confidence: 87%
“…Patients were mainly women, although the female/male ratio was lower than that reported for Spain and Europe ( 18 ), and had significant physical disability (mean EDSS score of 6.5). The most common MS phenotype was SPMS (65%), as reported in other studies ( 14 , 15 , 19 ). The mean number of symptomatic treatments used by patients increased over time.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The improvement in spasticity‐associated symptoms (e.g. spasms, pain, sleep disturbances) observed with nabiximols in randomized controlled trials and observational studies (Flachenecker et al., 2014b ; Markovà et al., 2019 ; Novotna et al., 2011 ; Vermersch & Trojano, 2016 ; Wade et al., 2004 ) suggested a need to look beyond spasticity itself when assessing clinical benefit in patients with MS. Retrospective analyses of real‐world data have since shown that spasticity‐associated symptoms may ameliorate during nabiximols treatment irrespective of the extent of improvement in a patient's spasticity (Patti et al., 2022 , 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…A recent Cochrane review concluded that, compared with placebo, nabiximols probably reduces the severity of MS-related spasticity in the short-term, but the effect on chronic pain, health-related QoL, and drug tolerance are uncertain [37 ▪ ]. A real-world evidence study of nabiximols in MS patients with resistant spasticity showed beneficial effect on spasticity-plus syndrome, that is, spasticity associated with pain, sleep disturbances, and spasm/cramp [38].…”
Section: Treatment Of Spasticitymentioning
confidence: 99%